Management for lymphatic malformations of head and neck - Yang, Weijia; Wang, Huaijie; Xie, Chong; Lin, Weilong; Wang, Peihua; Guo, Zhengtuan (Frontiers in Neurology, 2024)
Background: To explore the management of lymphatic malformation in head and neck.Methods: This is a retrospective study at a single center. Data on demographic, surgery, sclerotherapy and follow-up information were collected from our Vascular Anomalies Center database. Patients with lymphatic malformation of head and neck who had undergone surgery and sclerotherapy between March 2020 and March 2024 were included. . Results: There were 94 patients in this study, The lesion sites included head (n=60), tongue (n=7), neck (n=41), pharynx (n=7), and head and neck(n=7). Symptoms included bleeding (n=6), infection (n=2), dyspnea (n=2), dysphonia (n=4), and dysphagia (n=4). Lymphatic malformation included macrocystic (n=61), microcystic (n=12) and mixed(n=21). Surgeries for LM included radical resection, subtotal or partial resection and staged surgeries. Sclerotherapies included bleomycin monotherapy and combined sclerotherapy with ethanol and bleomycin, under ultrasound or fluoroscopy guidance. The follow-up period was from 3 months to 1 year. The therapeutic effect was evaluated according to the size of the treatment area. 55 patients, 21 patients, 11 patients and 7 patients were evaluated with excellent, good, moderate and no response, respectively.Surgical resection, sclerotherapy and the combination of the two are efficacious treatment modalities for head and neck LM. Combined with oral drugs and other new therapies may be warranted in future for challenging conditions.